2019
DOI: 10.1017/ice.2019.247
|View full text |Cite
|
Sign up to set email alerts
|

Impact of FDA black box warning on fluoroquinolone and alternative antibiotic use in southeastern US hospitals

Abstract: We analyzed antibiotic use data from 29 southeastern US hospitals over a 5-year period to determine changes in antibiotic use after the fluoroquinolone US Food and Drug Administration (FDA) advisory update in 2016. Fluoroquinolone use declined both before and after the FDA announcement, and the use of select, alternative antibiotics increased after the announcement. Fluoroquinolones are among the 4 most commonly prescribed antibiotic classes. 1,2 Postmarketing reports of serious adverse events linked to fluoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 6 publications
3
24
0
Order By: Relevance
“…Finally, it is unclear whether fluoroquinolones could be a preferred substitute choice given that the available information is scarce and poorly informative [10,12]. Furthermore, current recommendations warn against their widespread use for safety concerns; an issue which was not examined by the authors [15].…”
Section: Cephalosporin Restrictionmentioning
confidence: 99%
“…Finally, it is unclear whether fluoroquinolones could be a preferred substitute choice given that the available information is scarce and poorly informative [10,12]. Furthermore, current recommendations warn against their widespread use for safety concerns; an issue which was not examined by the authors [15].…”
Section: Cephalosporin Restrictionmentioning
confidence: 99%
“…No new antibiotic classes, particularly those active against the challenging Gram-negative pathogens, have been introduced since the introduction of the fluoroquinolones. At the same time, serious resistance and safety concerns over several commonly used classes, including the fluoroquinolones (7)(8)(9) and polymyxins (10)(11), have severely narrowed safe and effective options for the treatment of these life-threatening infections (4).…”
mentioning
confidence: 99%
“…The FDA specifically recommends not using this class for uncomplicated UTIs [22]. One study showed no change in fluoroquinolone prescribing for outpatient uncomplicated UTIs following the 2016 boxed warning [24], however another study demonstrated a decreased number of fluoroquinolone prescriptions in the inpatient setting for all infections [25]. In our qualitative analysis, residents and community providers seemed to be aware of these warnings, however they did not appear to have a major influence on prescribing patterns.…”
Section: Discussionmentioning
confidence: 73%